SYNTHESIS OF GRAPHENE OXIDE FROM SAGO WASTE FOR REMOVAL OF LEAD(II) IONS IN WATER - Dayang Norafizan, Awang Chee; Nur Afiqah, Kamaludin; Lucy, Sylvester; Muhammad Shamil, Soffian; Faezrul Zackry, Abdul Halim; Claudeareena Garlding, Malien; Mohamed Afizal, Mohamed Amin (UMT Press, 2025)
The goal of this study was to produce graphene oxide (GO) from sago hampas for the removal of lead (II) ions in water. The utilisation of sago hampas may promote sustainable practices for GO production using renewable biomass, thus reducing carbon footprint. The GO was made using a modified Hummers’ technique, which resulted in a highly oxidised material with many functional groups. The synthesised GO was characterised using Fourier-transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscopy (SEM). Batch adsorption tests were performed to evaluate the removal efficiency. The effect of pH, contact time, and initial Pb concentration was investigated during the optimisation process. The outcomes showed that GO had exceptional adsorption capabilities, eliminating over 95% of the Pb at its maximum efficiency. The adsorption kinetics pseudo-second-order model with a regression coefficient of R2 = 0.9999 illustrated a chemical adsorption mechanism. A monolayer adsorption mechanism is suggested by the equilibrium data’s good fit to the Langmuir isotherm (R2 = 0.9588). With its large surface area, abundance of functional groups, and strong adsorption affinity, the synthesised GO showed promising properties as an adsorbent for removing Pb from wastewater. This work provides critical knowledge for developing effective and ecologically responsible heavy metal removal adsorbents.